Propagator Method using PARAFAC Model for Two Dimensional Source Localization - N. Tayem; K. Majeed; A. A. Hussain (Radioengineering, 2018)
In this paper, we addressed the problem of estimating the two-dimensional (2D) Direction of Arrival (DOA) elevation and azimuth angles for multiple sources. The proposed method employs Propagator Method (PM) in conjunction with parallel factor (PARAFAC) model using a new antenna array configuration. The proposed method overcomes two main drawbacks in the existing 2D DOA schemes: use of high computation eigenvalue decomposition (EVD) or singular value decomposition (SVD), and complex pair-matching methods for elevation and azimuth angles in case of multiple sources. Therefore, significant reduction in computational load and complexity are achieved. Computer simulations demonstrate the effectiveness of the proposed method.